PFM.19 Trisomy 18 and 13 screening changes in Scotland. (9th June 2014) - Anderson, L; Villiers, M; Brown, L; Gibson, J
Abstract : All women in Scotland are offered first trimester screening combining ultrasound nuchal translucency measurement and free ßhCG and PAPPA-A levels to calculate their risk for Down's syndrome. Second trimester screening may then be offered due to failed NT measurements or later gestation. Although pregnancies affected by Trisomy 13 and 18 are much rarer it is possible to calculate a risk using the same tests. We have discontinued reporting high Trisomy 18/13 risks based on the same biochemical markers following indication that second trimester ultrasound was more sensitive and specific test. 1 Our aim was to determine those patients disadvantaged by changes to the screening programme. We identified confirmed cases of Trisomy 18 and 13 within the West of Scotland then by accessing genetics biochemical database we retrospectively calculated their biochemical screening risk from blood results previously used for T21 screening. Results: Indicate 4 patients potentially missed early detection (T18) with current screening guidelines and none for T13 from retrospective analysis (Table 1 ) 3 were CUBS with normal NT (1.3–2.9) and one second trimester result (uE3, Inhibin, AFP, HCG) Discussion: Within Scotland it is reassuring for patients that Trisomy 18/13 cases are rare. As a small retrospective audit this gives us helpful data that following changes to screening programme the numbers are few. As clinicians it is helpful to know we are not currently adversely affecting our current population with late diagnoses of these chromosomal abnormalities. Reference: NHS Fetal Anomaly Screening Programme